Research and artificial cardiac stimulation. II. clinical aplication - Ricardo Michielin Sant’anna, Joao (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
Research may help engineers to develop new technology for implantable devices, surgeons to create new operative techniques and physicians to evaluate belter the results of cardiac stimulation such as: mortality, morbidity, survival probability and functional improvement; evaluation of implantable prosthetic devices and definition the adequate stimulation mode for individual patientes. Research help to improve the surgical results and may also helps the surgeon, the physician and the technician to solve specific problems, specially in those cases where Dr. Kirklin’s program is employed.